MENCARI PROFOUND KNOWLEDGE TENTANG PERILAKU KERJA PENDIDIK - Desy Aniqotsunainy (Jurnal Al-Manar, 2015)
Perfection of worship as a manifestation hablumminallah be obtained when Hablumminannas done with humility and always respect others. Educator profession as one of the prototype and systematics are unique and original. Unique because educators sincerity manifested in every educator behavior. Original because of instinct, and the bodies educator ratio is a creation god that benefit everyone.